Evaluation of a Cold-Mixed High-Performance Polyurethane Mixture - Sun Min; Yufeng Bi; Mulian Zheng; Sai Chen; Jingjing Li (Advances in Materials Science and Engineering)
The energy consumption and greenhouse gas emission of asphalt pavement have become a very serious global problem. The high-temperature stability and durability of polyurethane (PU) are very good. It is studied as an alternative binder for asphalt recently. However, the strength-forming mechanism and the mixture structure of the PU mixture are different from the asphalt mixture. This work explored the design and performance evaluation of the PU mixture. The PU content of mixtures was determined by the creep slope (K), tensile strength ratios (TSR), immersion Cantabro loss (ICL), and the volume of air voids (VV) to ensure better water stability. The high- and low-temperature stability, water stability, dynamic mechanical property, and sustainability of the PU mixture were evaluated and compared with those of the stone matrix asphalt mixture (SMA). The test results showed that the dynamic stability and bending strain of the PU mixture were about 7.5 and 2.3 times of SMA. The adhesion level of PU and the basalt aggregate was one level greater than the limestone, and basalt aggregates were proposed to use in the PU mixture to improve water stability. Although the initial TSR and ICL of PU mixture were lower, the long-term values were higher; the PUM had better long-term water damage resistance. The dynamic modulus and phase angles (φ) of the PU mixture were much higher. The energy consumption and CO2 emission of the PU mixture were lower than those of SMA. Therefore, the cold-mixed PU mixture is a sustainable material with excellent performance and can be used as a substitute for asphalt mixture.